Management Problems in Implementing Development Works as Perceived by the NGOs: A Case Study in Nagaland, India - M. N. Odyuo , N. K. Patra and A. K. Makar, (Indian Journal of Extension Education, 2017)
This study aims to report on management problems in implementing development works as perceived by the NGOs'employees and measures suggested for improvement in Nagaland, India. In this study 45 NGOs were selected and fromeach NGO one higher level of employee was interviewed as respondent. The functional areas of developmentmanagement of developmental organizations were taken into consideration in this study viz. Planning, Financing,Organizing and Leading. The respondents were asked open ended questions to mention most important problems for eachof the functional area of management which they were facing and also to suggest measures for organizationaleffectiveness. Important identified problem(s) are donors terms of support and plan not matching properly, untimely andirregular fund flow, lack of technical staff and frequently relinquishing the organization, lack of proper office space andfurniture, lack of coordination between NGO and Govt. development functionaries, lack of regular supervision of dailyactivities in different areas and language problem, and suggestion(s) against the problems are - Flexibility in plan andscope of modification as per requirement, regular and timely fund flow, consultancy service from resource personnel, GONGOs collaboration, Popularization of Nagamese Language to address the language and communication problem